Counselling and spiritual accompaniment : bridging faith and person-centred therapy - Thorne, Brian, 1937- (Chichester, West Sussex : Wiley Blackwell, 2012)
'Counselling and Spiritual Accompaniment presents the key spiritually-focused writings of Brian Thorne, one of the most influential thinkers on the convergence of spirituality with counselling, along with new material reflecting his recent work in spiritual accompaniment. Reflects the increasing focus on spiritual issues as an essential part of therapy. Represents the culmination of an intellectual quest, undertaken by the most senior figure in the field, to integrate spirituality with counselling and the person-centred approach. Features chapters that span thirty years of work, along with new writings that bring readers up to date with the author's most recent work in spiritual accompanimen. An invaluable guide for counsellors and therapists who acknowledge the importance of spirituality to their clients, but doubt their abilities to help in this area'--Provided by publisher.
pt. I From: Person-centred Counselling: Therapeutic and Spiritual Dimensions -- Introduction -- ch. 1 In Search of Value and Meaning (1979) -- ch. 2 Intimacy (1982) -- ch. 3 Quality of Tenderness (1985) -- ch. 4 Blessing and the Curse of Empathy (1989) -- ch. 5 Carl Rogers and the Doctrine of Original Sin (1990) -- ch. 6 Carl Rogers: The Legacy and the Challenge (1990) -- ch. 7 God Who Comes: Good Friday 1946 (1991) -- pt. II From: Person-centred Counselling and Christian Spirituality -- Introduction -- ch. 8 Two Carls -- Reflections on Jung and Rogers (1983) -- ch. 9 Personality of Jesus and the Process of Therapy (1991) -- ch. 10 Spirituality and the Counsellor (1993) -- ch. 11 Julian of Norwich: Radical psychotherapist (1993) -- ch. 12 Jesus, the Incarnation of Holiness (Three Sermons, 1993) -- ch. 13 Developing a Spiritual Discipline (1994) -- ch. 14 Counsellor as Prophet (1994) -- ch. 15 Counselling and the Spiritual Journey (1997) -- pt. III From: The Mystical Power of Person-Centred Therapy -- Introduction -- ch. 16 Human Person: Hope or Despair? -- ch. 17 Person-centred Therapist as Secular Priest and Prophet -- ch. 18 Spiritual Discipline of the Person-centred Therapist -- ch. 19 Use of Self -- ch. 20 Intimacy and Sexuality -- ch. 21 Àlive Alive' -- ch. 22 When the World Stopped Turning -- pt. IV Ceasing to be a Therapist -- Prologue -- ch. 23 Heart's Surrender (2005) -- ch. 24 Counsellor and the Lay Canon: Different Routes but the Same Journey (2007) -- ch. 25 Collision of Worlds (2009) -- ch. 26 Fully Human Jesus (2009) -- ch. 27 Sacred Intimacy: Spiritual Accompaniment for our Times (2010) -- ch. 28 In Correspondence (2010).
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Person-Centered Therapy; Counseling; Spirituality; Spiritual direction; Counseling -- Religious aspects; SELF-HELP -- Substance Abuse & Addictions -- Drug Dependence; SELF-HELP -- Substance Abuse & Addictions -- General; SELF-HELP -- Twelve-Step Programs; Counseling -- Religious aspects; Spiritual direction; Electronic books